RESEARCH OF HARDWARE EXPENSES IN MICROPROGRAM FINAL-STATE MACHINE WITH DATAPATH OF TRANSITIONS - Babakov, R. M. (Radio Electronics, Computer Science, Control, 2018)
Contex. The problem of determining the hardware expenses in the logical circuit of a microprogram final-state machine with a canonical structure and a microprogram final-state machine with datapath of transition and various ways of generating of codes of transition operations was solved. Objective. The goal of the work is the obtaining of analytical expressions for determining the hardware expenses in the investigated structures of microprogram final-state machine depending on parameters of the automaton when using the elemental basis of programmable logical integrated circuits. Method. Based on results of HDL simulation, the experimental values of hardware expenses in typical functional blocks of digital devices are obtained. As a unit of measurement of hardware expenses, LUT elements, which are regular structural elements of the FPGA, are used. Among the typical functional blocks, a combinational logical circuit, a multiplexer, an arithmetic-logical operation circuit, and a register are investigated. By approximating the experimental data, analytical expressions for determining the hardware expenses in typical functional blocks, depending on the parameters of the blocks, are obtained. By replacing the parameters of typical functional blocks with parameters of the structural blocks of the microprogram final-state machines being researched, the analytical expressions to determine the hardware expenses in typical functional nodes are transformed in analogous expressions for separate structural blocks of automata. Results. For each of the researched structures of microprogram final-state machines, analytical expressions for determining the total hardware expenses in the logical circuit of the automaton are obtained. Conclusions. Received analytical expressions take into account the structural features of the Mealy and Moore automata and can be used to solve the problem of determining the field of effective application of the microprogram final-state machine structures with datapath of transitions.